Enhancing Packaging Materials: A Microstructural Investigation of Graphene Dispersion on Polymer Surfaces - Renato Matroniani; Felipe T. Mabilia; Jéssica S. Santos; Shu H. Wang (Materials Research)
Graphene is a versatile constituent with many applications in novel materials demanding improved electrical conductivity and mechanical resistance. Another application reported in the literature is its use as a barrier agent to gases, lipids, and water vapor, due to its honeycomb basal structure. We report on a straightforward method to achieve the surface modification of different substrates by depositing a graphene dispersion. The graphene dispersion in N-methyl-2-pyrrolidone (NMP) was prepared by liquid-phase mechanical exfoliation of graphite flakes and characterized to be comprised by multilayer graphene (mG). Ordinary commercial substrates, films produced by the packaging industry, such as low-density polyethylene (LDPE), poly(ethylene terephthalate) (PET), paper, and cellophane (CEL) were treated by a mG dispersion using drip casting. Scanning electron microscopy (SEM) was carried out on these different substrates before and after mG coating. LDPE showed irregular mG covering and aggregation, compared to the uniform distribution in PET and cellophane films, that corroborates the results obtained from tape tests. UV-Vis transmittance indicated minimal interference from the graphene layer compared to the uncoated film. The results were discussed taking into account the interplay of the surface energy of the chemical substances involved. The different modified films might work as a barrier packaging films.